EcoHealth research in Southeast Asia: Past, now, and the ways forward - Hung Nguyen-Viet; Gilbert, Jeffrey; Dinh Xuan Tung; Mallee, H.; Unger, Fred; Grace, Delia (Veterinary Public Health Centre for Asia Pacific, 2013)
EcoHealth is one of the comprehensive concepts to look at health as an integrative component of the complex relation of human, animal and environment. Although it was introduced in South East Asia (SEA) late in 2000’s by IDRC, its development in the region shows a dynamics in the landscape of research and application of EcoHealth in various fields such as emerging and zoonotic diseases, agriculture and health, education and training. The objective of this presentation is to review EcoHealth activities in SEA of the last 10 years to address lessons learned, challenges and future of EcoHealth in the region. We analysed all the EcoHealth programmes, initiatives and projects (now called projects) that have been being implemented in the past 10 years with support of IDRC in SEA. Main considered EcoHealth projects are: APEIR (Asian Partnership on Emerging Infectious Diseases Research), EcoZD (Ecosystem Approaches to the Better Management of Zoonotic Emerging Infectious Diseases in SEA), EcoEID (EcoHealth emerging infectious diseases research in SEA), FBLI (Field Building Leadership Initiative in SEA), BECA (Building Capacity in EcoHealth for SEA). The level of Ecohealth characterised by how much “EcoHealth content” was analysed. The results showed that generally, EcoHealth has been well perceived and taken by partners, in particular academia, policy makers and communities and generated some good research results in the field of ZEIDs. Some projects focused purely on capacity, others on research or both. However, the challenges remain at the project design and implementation level but also on the available capacity and coordination to develop EcoHealth research and teams in the countries as well as the issue of EcoHealth scaling-up. Finally we will present the ways forward of EcoHealth from a regional perspective in terms of research, training and policy translation using EcoHealth in combination with One Health approach.